2017
DOI: 10.1096/fj.201601227r
|View full text |Cite
|
Sign up to set email alerts
|

Human leucine zipper protein promotes hepatic steatosisviainduction of apolipoprotein A‐IV

Abstract: The molecular mechanism of stress-induced hepatic steatosis is not well known. Human leucine zipper protein (LZIP) regulates the expression of genes involved in inflammation, cell migration, and stress response. The aim of this study was to determine the regulatory role of LZIP in stress-induced hepatic steatosis. We used a microarray analysis to identify LZIP-induced genes involved in hepatic lipid metabolism. LZIP increased the expression of apolipoprotein A-IV (APOA4) mRNA. In the presence of stress inducer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…In agreement with this, we identified several cancer‐related over‐expressed genes, including Cscbp2 , Apoa4 , Anxa2 , Serpine1 , Igfbp1 , and Tubb2a , that were associated with chromatin‐accessible regions in NASH‐derived HCC. It has been reported that up‐regulation of these genes may have significance in the hepatocarcinogenic process, in general, and in the pathogenesis of NAFLD and NAFLD‐associated liver carcinogenesis, in particular …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In agreement with this, we identified several cancer‐related over‐expressed genes, including Cscbp2 , Apoa4 , Anxa2 , Serpine1 , Igfbp1 , and Tubb2a , that were associated with chromatin‐accessible regions in NASH‐derived HCC. It has been reported that up‐regulation of these genes may have significance in the hepatocarcinogenic process, in general, and in the pathogenesis of NAFLD and NAFLD‐associated liver carcinogenesis, in particular …”
Section: Discussionmentioning
confidence: 99%
“…Apoa4 is a critical gene involved in the regulation of multiple metabolic pathways, including lipid absorption, lipid metabolism, and glucose homeostasis . Emerging evidence suggests a critical role of apolipoproteins, including APOA4, in the pathogenesis of NAFLD Specifically, Kang et al demonstrated that over‐expression of APOA4 promotes lipid accumulation in the liver, and Qin et al reported that the level of APOA4 protein was increased in the genetically obese ( ob/ob ) mice. Furthermore, a marked upregulation of APOA4, as well as SERPINE1 and IGFBP1, has been demonstrated in patients with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations